The impacts of dietary sphingomyelin supplementation on metabolic parameters of healthy adults: a systematic review and meta-analysis of randomized controlled trials - Li, Chen-Zi; Wu, Li-Mei; Zhu, Chen-Xi; Du, Huan-Yu; Chen, Guo-Xun; Yang, Fang (Frontiers in Nutrition, 2024)
Background: Studies have shown that sphingomyelin (SM) and its metabolites play signaling roles in the regulation of human health. Endogenous SM is involved in metabolic syndrome (MetS), while dietary SM supplementation may maintain lipid metabolism and prevent or alleviate MetS. Therefore, we hypothesized that dietary SM supplementation is beneficial for human health.In order to examine the impacts of dietary SM on metabolic indexes in adults without MetS, we performed a meta-analysis to test our hypothesis.Methods: A comprehensive search was performed to retrieve randomized controlled trials that were conducted between 2003 and 2023 to examine the effects of dietary SM supplementation on metabolic parameters in the Cochrane Library, PubMed, Web of Science, Embase, and ClinicalTrials.gov databases. RevMan 5.4 and Stata 14.0 software were used for meta-analysis, a sensitivity analysis, the risk of bias, and the overall quality of the resulted evidence.Results: Eventually, 10 articles were included in this meta-analysis. Dietary SM supplementation did not affect the endline blood SM level. When compared to the control, SM supplementation reduced the blood total cholesterol level [MD:-12.97, 95% CI: (-14.57, -11.38), p < 0.00001], low-density lipoprotein cholesterol level [MD:-6.62, 95% CI: (-10.74, -2.49), p = 0.002], and diastolic blood pressure [MD: -3.31; 95% CI (-4.03, -2.58), p < 0.00001] in adults without MetS. The supplementation also increased high-density lipoprotein level [MD:1.41, 95% CI: (0.94, 1.88), p < 0.00001] and muscle fiber conduction velocity [MD: 95% 1.21 CI (0.53, 1.88), p = 0.0005]. The intake of SM had no effect on the blood phospholipids and lyso-phosphatidylcholine, but slightly decreased phosphatidylcholine, phosphatidylethanolamine, and phosphatidylinositol concentrations. Dietary SM supplementation reduced insulin level [MD: -0.63; 95% CI (-0.96, -0.31), p = 0.0001] and HOMA-IR [MD: -0.23; 95% CI (-0.31, -0.16), p < 0.00001] without affecting blood levels of glucose and inflammatory cytokines.Overall, dietary SM supplementation had a protective effect on blood lipid profiles and insulin level, but had limited impacts on other metabolic parameters in adults without MetS. More clinical trials and basic research are required.